Cybersports education in Ukraine: current state and development prospects - Tsyhanovska, Nataliia; Honchar, Viacheslav; Danilyan, V.; Piatysotska, S. (My University, 2022)
The material of the study is the scientific literature and Internet sources, which highlight the current state of cybersport and cybersport education in Ukraine. Research methods: analysis, generalization and systematization of data; historical, logical, problem-search, prognostic.
Keywords: кіберспорт, e-sports